Analysis of hospital liquid waste management system (case study of Rumah Sakit Mata Masyarakat Jawa Timur) - Kusuma, Julian Daffa; Fasya, Abdul Hakim Zakkiy (Universitas Nahdlatul Ulama Surabaya, 2025)
Wastewater originating from hospital waste is a very potential source of water pollution. Based on assessment data, the pollutant content in waste water, the impact and volume of waste produced and the low efficiency of hospital Waste Water Treatment Installations (IPAL) in Indonesia. Making hospital waste water needs to be treated with appropriate processing technology. Therefore, an analysis of the liquid waste management system was carried out in the waste water management installation at the East Java Community Eye Hospital. This research uses a qualitative method with a case study design. This research involved 1 informant as a resource person, The data collection techniques in this study were observation and in-depth interviews, which were then analyzed using method triangulation. This research shows that in the output process, laboratory test results for waste water samples were obtained for all parameters which were below the threshold values except for temperature, ammonia, phosphate and coliform levels which exceeded the predetermined threshold values. Researchers concluded that the liquid waste management system at RSMM East Java was completely adequate both in terms of input, process and output, but there were several systems that did not work optimally. The advice given to hospitals is to regularly check waste inlets, facilities and infrastructure, plan further processing, and increase human resources.